Strategi Manajemen Sektor Publik Pemerintah Desa Sindangsari dalam Penanganan Corona Virus Disease 2019 (COVID-19) - Yeni Widyastuti; Arenawati Arenawati; Listyaningsih Listyaningsih (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2021)
COVID 19 is more than just health crisis but also a humanitarian crisis in every country of the world, including creating threats in the social and economic fields. In a more diverse context, the COVID 19 pandemic has also caused disruption of social services, social activities, financial resources and economically vulnerable groups of people with low income sources who will find it difficult to access health services, difficulty meeting nutritious food needs including staple foods. Sindangsari Village as a form of public sector organization, that provision of social security and public service administration need to carry out a strategy the most effective intervention to help slow down the transmission of the COVID 19 virus at the community level. The strategy involves all agencies in village structure, RT/RW, as well as communities and local residents. These strategies are (1) Strategies for Implementing Main Duties and Government Function in Public Service; (2) Strategies for Coordination, Disseminating and Increasing Public Awareness and Health Service Preparation and (3) Strategies for Meeting the Basic Need of Community, Procedure and Mechanism during the COVID 19 pandemic.